All for one and one for all : encouraging prosocial behaviours through brand-convened consumer groups - Champniss, Guy (Cranfield University, 2013)
Academic and practitioner interest in sustainable consumer behaviour continues to grow. Yet the focus remains on marketing appeals based on awareness raising, perspective taking and concern. Whilst such an approach may be suitable for an established niche of committed consumers, it continues to be inappropriate for the majority. Situated within the debates on consumer behaviour, prosocial behaviour, brand communities and social identity theory, this study proposes an alternative route towards sustainable behaviours. This study focuses on such behaviours via the brand's formation of 'pop-up' consumer groups, and the subsequent influences these groups can exert on group members. Adapting aspects of social identity theory and self-categorisation theory, the study uses a novel field-based experiment to manipulate consumers into specific group structures (high/low group salience; normal/sustainable group goals) and measures the effects of these manipulations on prosocial behaviours both within and beyond the group. The effects on the consumer brand relationship are also observed. The results show first that such rapid group formation can lead to prosocial behaviours. Second, the results show that social identification with the group mediates the relationship between group salience and prosocial behaviours, but does not mediate the relationship between group goal and prosocial behaviours. Hence, it is suggested that two distinct processes are at work: social identity influence and social norm influence. Third, the study shows that group manipulations increase the consumer brand connection. Fourth, the study proposes novel distinctions between money and time as tradeable consumer resources, and suggests how the context of the request for these resources may alter the propensity to give. This study is the first of its kind to create a novel, minimal and temporary group within a natural consumer context, in order to encourage prosocial behaviour. The creation of these ‘pop-up’ groups provides an original contribution to both theory and practice.